ASSOCIATION OF HELICOBACTER PYLORI INFECTION AND GASTROINTESTINAL DISEASE IN CHILDREN - Vanya Nedkova-Milanova; Zornitsa Gorcheva; Ivaylo Pakov; Milena D. Karcheva (Peytchinski Publishing, 2024)
Purpose: The purpose of this study was to assess the association between some clinical and epidemiological factors and the prevalence of Helicobacter Pylori (H. pylori) infection in children visited a paediatrics ambulatory care at University Hospital - Pleven for various symptoms pointing to gastritis and peptic ulcer. Materials and methods: an epidemiological study was conducted for the period June-September 2023. In total, 133 children aged from 2 to 18 years were evaluated. All visited a paediatrics ambulatory care at University Hospital - Pleven for various complaints pointing to gastritis and peptic ulcer. Results: During the study period, we recruited a total of 133 children and adolescents (age range 2-18 years, mean age 9.36 ± 4.08 years). More patients were males (54.14%) than females (45.86%). The most frequent symptoms were abdominal pain (51.88%), nausea and vomiting (21.80%), and losing weight (10.53%). The social status of the families is good - parents with a university education predominate (49.62%). There are risk factors for the presence of infection and the development of gastritis and ulcers in children: family history of H. pylori infection (47.37%) and use of unsuitable foods (48.87%). A high positivity is found for H. pylori (40.43%). Conclusions: Early diagnosis and etiological treatment of H. pylori infection reduces the risk of developing gastric complications like chronic gastritis, ulcer diseases and gastric cancer.